Work Engagement as mediator between perceived participation, supervisor support and altruistic behaviors : empirical results from the italian social enterprise sector (2013)
ABSTRACT: This research note presents an empirical study conducted in a number of social cooperatives (SCoops). Democratic governance has been identified as a defining aspect of this kind of social enterprise. Using the work and organizational psychology approach, the authors studied the effects of democratic governance and supervisor support on workers’ engagement and organizational citizenship behaviors. The convenience sample technique was used for gathering the data. Data was collected with a self-administered questionnaire. The sample consisted of 258 participants from three different Scoops situated in northern Italy. Statistical analysis results suggest that worker’s perceived participation and supervisor support enhance work engagement, and subsequently, altruistic behaviors. Finally, the authors comment on the limitations of the study giving methodological suggestions for future empirical research.